Higher Degree Research at Australian Universities: Responding to Diversity in Engineering and Information Technology - Shamim, S.; Woodman, K.; Trevelyan, J.; Taji, A.; Narayanaswamy, Ramesh; Silva, P.; Yarlagadda, P. (The Engineering & Science Education Research (ESER) group, Faculty of Engineering & Industrial Sciences, Swinburne University of Technology, Melbourne, Australia, 2012)
Background: There is increasing enrolment of international students in the Engineering and Information Technology disciplines and anecdotal evidence of a need for additional understanding and support for these students and their supervisors due to differences both in academic and social cultures. While there is a growing literature on supervisory styles and guidelines on effective supervision, there is little on discipline-specific, cross-cultural supervision responding to the growing diversity. In this paper, we report findings from a study of Engineering and Information technology Higher Degree Research (HDR) students and supervision in three Australian universities. Purpose: The aim was to assess perceptions of students and supervisors of factors influencing success that are particular to international or culturally and linguistically diverse (cald) HDR students in Engineering and Information technology. Design/Method: Online survey and qualitative data was collected from international and cald HDR students and supervisors at the three universities. Bayesian network analysis, inferential statistics, and qualitative analysis provided the main findings.Results: Survey results indicate that both students and supervisors are positive about their experiences, and do not see language or culture as particularly problematic. The survey results also reveal strong consistency between the perceptions of students and supervisors on most factors influencing success. Qualitative analysis of critical supervision incidents has provided rich data that could help improve support services. Conclusion: In contrast with anecdotal evidence, HDR completion data from the three universities reveal that international students, on average, complete in shorter time periods than domestic students. The analysis suggests that success is linked to a complex set of factors involving the student, supervision, the institution and broader community.